2022
DOI: 10.1097/meg.0000000000002490
|View full text |Cite
|
Sign up to set email alerts
|

Clinical remission in paired phase two and three studies in inflammatory bowel disease: a systematic review with meta-analysis

Abstract: Discrepancies in phase two and three studies can result in significant patient and financial burden, as well as the nonapproval of potentially efficacious drugs. We aimed to determine whether this discrepancy exists for clinical trials in inflammatory bowel disease (IBD). Electronic databases (MEDLINE and Embase) and clinical trial repositories were searched from 1 January 1946 to 12 March 2021, for paired phase two and three studies of advanced therapies for Crohn’s disease and ulcerative colitis. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
(204 reference statements)
0
7
0
Order By: Relevance
“…In UC trials, the primary endpoint was clinical remission for 14 studies (five phase 2 and 9 phase 3) and clinical response for one phase 2 and two phase 3 studies. Clinical outcomes were mostly evaluated using the full MS except for the upadacitinib trials and the mirikizumab phase 3 trial (using the adapted MS) and for one other study using the Ulcerative Colitis Clinical score 8 . Definitions used for clinical outcomes are detailed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In UC trials, the primary endpoint was clinical remission for 14 studies (five phase 2 and 9 phase 3) and clinical response for one phase 2 and two phase 3 studies. Clinical outcomes were mostly evaluated using the full MS except for the upadacitinib trials and the mirikizumab phase 3 trial (using the adapted MS) and for one other study using the Ulcerative Colitis Clinical score 8 . Definitions used for clinical outcomes are detailed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical outcomes were mostly evaluated using the full MS except for the upadacitinib trials and the mirikizumab phase 3 trial (using the adapted MS) and for one other study using the Ulcerative Colitis Clinical score. 8 Definitions used for clinical outcomes are detailed in Table 2 . Among the six phase 2 trials, 4 were positive for the primary endpoint, followed by at least one positive phase 3 trial for the primary outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment effect sizes are dependent on the difference in event rates in the active treatment arm and the placebo arm—the latter was ignored in previous studies comparing phase 2 and 3 trials in rheumatology and IBD ( 8 , 56 ). Smaller-than-expected treatment effect sizes across clinical trial phases can be the result of lower rates of remission in the active arm or higher rates of remission in the placebo arm, or both.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis exploring clinical remission in paired phase 2 and 3 studies in IBD trials was recently published ( 56 ). No difference in rates of clinical remission between trial phases was found.…”
Section: Discussionmentioning
confidence: 99%